2020
DOI: 10.1002/ijgo.13464
|View full text |Cite
|
Sign up to set email alerts
|

Integration of family planning services into health care for HIV‐positive women in Botswana

Abstract: In an HIV clinic in Botswana, provision of on-site contraceptive services for women encouraged family planning discussions and increased interest in LARC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Pertaining the method of contraception, the main method of contraception was injectable contraceptives (45.8%) because it's easy to use, administer, and can be used without the partner's knowledge as well as easy follow up which is once every 3 months. This is consistent with the findings of a similar study conducted in South Africa by [22] who reported that women were interested in using injectable because it can be used without their partners' awareness and injectable has less tension than pills like swallowing and remembering of timing of pills swallowing.…”
Section: Service Delivery Factors Influencing the Utilization Of Fp Services By Plwhiv Attending Taso Masakasupporting
confidence: 91%
“…Pertaining the method of contraception, the main method of contraception was injectable contraceptives (45.8%) because it's easy to use, administer, and can be used without the partner's knowledge as well as easy follow up which is once every 3 months. This is consistent with the findings of a similar study conducted in South Africa by [22] who reported that women were interested in using injectable because it can be used without their partners' awareness and injectable has less tension than pills like swallowing and remembering of timing of pills swallowing.…”
Section: Service Delivery Factors Influencing the Utilization Of Fp Services By Plwhiv Attending Taso Masakasupporting
confidence: 91%
“…Description of studies : Seventeen studies were included in the systematic review: four RCTs and one two-year follow up analysis of an RCT 18 35 36 37 38 , two non-RCTs 39 40 , six pre-post-intervention studies 41 42 43 44 45 46 , one cohort study 47 and three cross-sectional comparison studies 48 49 50 . Among these studies, 15 belonged to African countries: four from Kenya 36 38 47 50 and two from South Africa 35 42 , Uganda 37 48 and Malawi 44 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Among these studies, 15 belonged to African countries: four from Kenya 36 38 47 50 and two from South Africa 35 42 , Uganda 37 48 and Malawi 44 49 . One study each belonged to Zimbabwe 39 , Nigeria 40 , Tanzania 41 , Botswana 45 and Zambia 46 . Apart from the African countries, one study each belonged to India 18 and the United Kingdom 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Hawkins et al reported on women's desire for wanting to utilize LARC pre-intervention compared to post-intervention ( 37 ). A positive association between integration and more positive attitudes toward FP was identified with the desire to use LARC at 6% at pre-intervention compared to 29% at the endpoint ( p < 0.001) ( 37 ).…”
Section: Resultsmentioning
confidence: 99%